BRAC Education Program (BEP): progress report, June - November 2002 - BRAC (© BRAC, 2016)
1. BEP organogram 2. BEP at a glance 3. Financial report 4. LFA based report 5. Progress on implementation of MTR recommendations 6. BEP activities by funding sources 7. Annexure for financial report.